Vaccination against Measles in Patients with Oncological Disease - S. M. Kharit; I. V. Fridman; A. A. Ruleva (Эпидемиология и вакцинопрофилактика, 2024)
Relevance. Growing distrust of vaccines around the world, a decrease in vaccination rates have led to an increase in the incidence of measles and a rise in the vulnerability of people with immunodeficiency status. The aim. To study the efficacy and safety of measles vaccination in children with oncohematological diseases. Materials & methods. The study involved 107 children: 74 of them with a history of acute lymphoblastic leukemia and 33 with solid tumors. All children had a history of receiving standardized polychemotherapy. In all the subjects, the vaccination history was studied, the titers of specific antibodies to measles were determined. Children with non-protective levels of antibodies (53 children) were subsequently vaccinated against measles. Results and discussions. Of the 107 children examined, before cancer, 99 (92.5%) were vaccinated against measles, of which 68 (68.7%) patients were only vaccinated, and 31 (31.3%) had vaccination and revaccination. Protective titers of antibodies against measles were preserved in 51 people (51.5%), and 48 (48.5%) were seronegative. When assessing immunogenicity on days 14, 45 after the introduction of the vaccine, it turned out that by day 14, 27 out of 53 children (50.9%) developed measles antibodies, and by day 45, 33 out of 53 children (62.3%), the rest of the children did not developed a protective level of antibodies, including 3 of 6 revaccinated. Conclusion. Thus, children with malignant diseases, regardless of the number of previous vaccinations and the duration of the end of therapy, become unprotected or have low titers of antibodies to measles in 83.8%, and immunization after treatment is effective in 62.3% of cases.